Involving Young People with Disabilities in Post-school Transitions through Reflecting Teams. Methodological Reflections and Adaptations for More Participation in a Longitudinal Study - Fasching, Helga; Felbermayr, Katharina; Todd, Liz (International Journal of Educational and Life Transitions, 2023)
This paper analyses a participatory method to involve young people with disabilities in research by using reflecting teams. In the course of the longitudinal project “Cooperation for Inclusion in Educational Transitions” on the transition from school to work of young people with disabilities, we examined ways to increase the participation of these people in the design and content of reflecting team sessions. In this regard, the reflecting team, more often used in a counseling context, was adapted to provide a special form of group discussion for participatory research with young people with different disabilities. The paper describes and discusses the adaptations that were made in the reflecting team research process. These adaptations included giving these young people, rather than a researcher, a role as moderator, inviting increased visualization within the reflecting process, and using an outsider-witness approach. Finally, we discuss the potential of the reflecting team for our participatory research with young people with disabilities.